THF KEYNESIAN AND THE MONETARY APPROACH TOWARDS THE DYNAMICS OF FOREIGN EXCHANGE RESERVE THROUGh THE BALANCE OF PAYMENT INVESlIGATION AN EMPIRICAL STUDY IN INDONESIA ON THE PERIOD I983-2008 - Masdjojo, Gregorius N. (Proceeding Fakultas Ekonomi, 2014)
The main objective of this research is to analyze the effect of the change on the National Income, the Domestic Credit, the Exchange Rate and the Interest Rate to the change of the Foreign Exchange Reserve. The research analyze based on the Keynesian Balance of Pavmcnt Theory (KBPT) and the Monetary Approach to the Balance of Payment (MAHP) The KHPT was oriented to the short term analysis and the MABP was onented to the long temi analysis The data is analyzed by the Error Correction Model (ECM). The results showed that in thc long run the National Income, the Domcsuc Credit, the Exchange Rate and the Interest Rate can change the Foreign Exchange Reserve significantly partially and simultaneously. The results showed that the effect of the independent variables so the Foreign Exchange Reserve is the same as the hypotheses ofthc KHPT and MARlâ. It can be concluded from Error Correction Term (ECIâ) valuc that in indonesia the economy needs 6-7 quartals (1.5 years to reach the new equilibrium. Keywords: The Foreign Exchange Reserve, The Keynesian Balance of Payment Theory and The Monetary Approach to the Balance of Payment. The Error Correcnon Model